Results of hip arthroscopy in elite level water polo players with femoroacetabular impingement: return to play and patient satisfaction. Issue 1 (22nd January 2020) - Ramos, Nicholas; Youssefzadeh, Keon; Gerhardt, Michael; Banffy, Michael
Abstract: Water polo places significant stress on the hip joint requiring repetitive hip flexion and rotation to elevate the body out of water for passing, shooting and blocking. Femoroacetabular impingement (FAI) is common in water polo athletes; however, no study to date has investigated the results of hip arthroscopy in this patient population. The purpose of this study was to determine return to play rates and satisfaction following hip arthroscopy for FAI in a cohort of elite level water polo players. A retrospective review of our surgical database was performed. Collegiate water polo players with clinical and radiographic FAI who underwent hip arthroscopy were identified. Pre- and post-operative modified Harris hip scores (mHHSs) were obtained. Patient surveys were administered to determine return to play rates, level of return to play, timing of return and patient satisfaction. A Wilcoxon ranked sum test was performed to compare pre- and post-operative outcome scores. Ten patients met inclusion criteria. Average age was 19.5 years old (SD  ±1.08). All patients were male Division 1 collegiate water polo players. Median mHHS improved from 66.0 (SD  ±7.9) pre-operatively to 89.5 (SD  ±3.2) at average 1.6 years (range: 0.4–3.6 years) post-operatively. Patient survey responses demonstrated a 100% return to water polo and 100% return to the same level of play (NCAA Division 1) at mean 5.75 months (SD  ±1.8). All patients (10/10) reported being satisfied with their surgical result. Our study results, suggest that return to sport rates and patient satisfaction are high in water polo players who undergo hip arthroscopy for FAI.